2011
DOI: 10.1002/dc.21778
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human papillomavirus among women with abnormal cervical cytology in Kuwait

Abstract: This study investigates the distribution of human papillomavirus (HPV) in women with abnormal cervical cytology in Kuwait. Two hundred and ninety-eight (298) abnormal ThinPreps were taken from women seeking routine gynecological care and screened for HPV DNA by real-time PCR. HPV genotyping was determined by PCR-based sequencing. HPV DNA was detected in 152 women (51%), and 29 different HPV genotypes were detected, comprising 16 high-risk (HR) (16, 18, 31, 33, 35, 39, 45, 51, 53, 56, 58, 59, 66, 68, 73, 97), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 35 publications
(46 reference statements)
6
37
3
Order By: Relevance
“…The population-based type-specific prevalence of HPV 16 is ranging from around 2% to 4% in all regions [6]; however, HPV 16 infection is strongly associated with risk of cervical neoplasia and causes over 50% of cases of cervical cancer [4]. HPV 81 (equivalent to CP8304) is also reported to be associated with precancerous or cancerous lesions [18,19]. The prevalence of HPV 81 in worldwide population studies is not very high but HPV 81 is one of the most frequently observed HPV types in the HIV-positive patients [20,21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population-based type-specific prevalence of HPV 16 is ranging from around 2% to 4% in all regions [6]; however, HPV 16 infection is strongly associated with risk of cervical neoplasia and causes over 50% of cases of cervical cancer [4]. HPV 81 (equivalent to CP8304) is also reported to be associated with precancerous or cancerous lesions [18,19]. The prevalence of HPV 81 in worldwide population studies is not very high but HPV 81 is one of the most frequently observed HPV types in the HIV-positive patients [20,21].…”
Section: Resultsmentioning
confidence: 99%
“…Persistent infection with high-risk Alpha PVs is a prerequisite for the development of cervical cancer and its histological precursor, cervical intraepithelial lesions. Twelve HPVs (16,18,31,33,35,39,45, 51, 52, 56, 58, and 59) are classified by the International Agency for Research on Cancer as being carcinogenic to humans, with HPV 68 being recognized as probably carcinogenic. Several other HPV types (26,30,34,53,66,67,69,70,73,82,85, and 97) are possibly carcinogenic based on evolutionary similarity to the known cancer-causing types [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study of 298 women with abnormal cervical cytology in Kuwait [27], reported that as the severity of the cytological diagnosis increased the proportion of single infections decreased, while the proportion of multiple infections increased, and Fife et al [39] found 85.3% of multiple HPV infections in dysplasia and 61.9% in ASC-US, these last concluding that their data support a possible role for multiple HPV types in the development or progression of cervical dysplasia. This is an issue that requires further investigation.…”
Section: Discussionmentioning
confidence: 97%
“…In all geographical regions, HPV prevalence was highest in women younger than 35 years of age, decreasing in older women [26]. Regarding age distribution, 69% of all HPV infections were found in women aged 20-29 years [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The assay was carried out on 3 different plates, as described previously [23,24]. The first plate was used to determine the integrity of the target DNA by β-globin PCR assay, amplifying a target of a 268-bp fragment as described previously by Lum and Le Marchand [25].…”
Section: Methodsmentioning
confidence: 99%